Ketahanan Pangan Rumah Tangga Petani Kopi Arabika di Desa Kendenan Kecamatan Baraka Kabupaten Enrekang - Adi Candra Wijaya; Sri Mardiyati; Muh. Ikmal Saleh (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
The population in this study were 120 people and 25% of the sample was taken. Determination of the sample using simple random sampling technique. The samples obtained were 30 respondents. Analysis of the data used is the analysis of farm income and food expenditure analysis. The results showed that the total food and non-food expenditure of Arabica coffee farmers in Kendenan Village, Baraka District, Enrekang Regency was Rp. 5,461,733.00 per year for food expenditure and for food expenditure per month was Rp. 455,144.42. Meanwhile, non-food expenditure is IDR 5,020,100.00 per year and IDR 418,341.67 per month. The food security level of farmer households is categorized as food secure by 60% of farmers and those who are food insecure are 40% of farmers. Arabica coffee farmers in Kendenan Village, Baraka District, Enrekang Regency have a level of food security category.